Occupational exposures to engine exhausts and other PAHs and breast cancer risk: A population-based case-control study - Rai, R.; Glass, D.; Heyworth, J.; Saunders, C.; Fritschi, Lin (2016)
Background: Some previous studies have suggested that exposure to engine exhausts may increase risk of breast cancer. Methods: In a population-based case-control study of breast cancer in Western Australia we assessed occupational exposure to engine exhausts using questionnaires and telephone interviews. Odds Ratios (OR) and 95% Confidence Intervals (CI) were calculated using logistic regression. Results: We found no association between risk of breast cancer and occupational exposure to diesel exhaust (OR 1.07, 95%CI: 0.81-1.41), gasoline exhaust (OR 0.98, 95%CI: 0.74-1.28), or other exhausts (OR 1.08, 95%CI: 0.29-4.08). There were also no significant dose- or duration-response relationships. Conclusions: This study did not find evidence supporting the association between occupational exposures to engine exhausts and breast cancer risk.